Determinants of effective tax investigations in Malaysia from the tax authority's perspective - Raig, John Tensay Peter (Curtin University, 2015)
This study attempted to examine the determinants of effective tax investigations in Malaysia, from the tax authority’s (IRBM) perspective. It was conducted through two qualitative and one quantitative research methods. It was found that professional proficiency has the most significant influence on the effectiveness of tax investigation, followed by tax enforcement strategy and severity of tax penalties. Several implications were identified and would serve to help the IRBM to enhance its tax enforcement system.